A prática do marketing de relacionamento na conquista da lealdade do cliente médico cearense pela indústria farmacêutica - Lopes, Alfredo Saboya Dias (2012)
The purpose of this study was to observe the practices of marketing relationship developed by the pharmaceutical industry as a means of influencing the loyal behavior of physician customers. Faced with such a competitive market as pharmaceutical is, where the differences of product is becoming smaller, and competitors are fast to copy innovations and offer similar products at lower cost, laboratories have shifted their focus. While previously it was restricted to products with large investments in research and development of new drugs, now the pharmaceutical industry seeks to strengthen the client-company relationship as a way of gaining competitiveness in the market. This study was based on a survey conducted in São Paulo by Walmon Magalhães Leal, an exploratory qualitative research together with the pharmaceutical industry which has raised the main actions, benefits and services performed by large laboratories, as well as the performance of propagandist in managing relationship with doctors. Leal´s work (2004) identified the 10 most representative variables of marketing relationship used by the pharmaceutical industry to establish and develop good relationship with physicians. With this, 202 physicians were interviewed through a descriptive quantitative research, by means of closed questionnaire, in order to check how they evaluated practices of marketing relationship by pharmaceutical companies. The results of the questionnaires, according to the doctor´s answers, were classified into two distinct groups (doctors “loyal” and “non-loyal” to the pharmaceutical industry). The descriptive data analysis and testing of the premises to carry out the discriminant analysis, which was the data processing method chosen, it was found that the sample could not be subjected to a discriminant analysis, thus, we opted for Mann-Whitney´s non-parametric average comparison test to proof the hypothesis of this work. The first hypothesis, that the practices of marketing relationship companies influence the behavior of doctors´ loyalty was confirmed, since the level of agreement of the “loyal doctors” to the variable “frequency of visits”, “scientific information”, “financial aid”, “free sample” and “relationship with vendors” is statistically higher than the tally variables of “non-loyal doctors”. It was also tested the hypothesis that the doctors in the country side of the state tend to be more loyal to the pharmaceutical industry, because they perceive the role of propagandists as an important way to keeping up, since they do not have much access to scientific meetings as the doctors who reside in the capital city might have. This hypothesis could not be proven, because there was not a statistically significant difference of great concordance between loyal physicians in the country side and the capital. This work has contributed to expand the knowledge about the practice of marketing relationship in pharmaceutical companies and their influence on the loyalty of physicians, since this topic has not been studied yet.